[The old crater of Erebus, with an older crater in the background, British Antarctic Expedition, 1907-1909] (1907)
An explorer standing in an old crater of Mount Erebus.
Part of collection: Sir Douglas Mawson collection of Antarctic photographs.
Condition: Good.
Also available online
Published in: The heart of the Antarctic / by E.H. Shackleton. London : Heinemann, 1909.
Keywords: Explorers -- Antarctica -- Photographs; Volcanoes -- Antarctica -- Photographs; Erebus, Mount (Antarctica) -- Photographs